Distinctive Pattern of Cognitive Disorders During Multiple Sclerosis Relapse and Recovery Based on Computerized CANTAB Tests - Giedraitiene, Natasa; Kaubrys, Gintaras (Frontiers in Neurology, 2019)
Background: Cognition may be affected at least as seriously as physical function during multiple sclerosis (MS) relapse, however MS relapse related cognitive disorders are still underdiagnosed and poorly characterized. The limited number of paper-pencil tests were used for assessment and nevertheless some significant changes were found. Unlike the paper-pencil tests, computerized batteries and tests are more sensitive and highly standardized, produce instant scoring and can minimize the learning and practice effects on follow-up. We investigated the cognition during MS relapse with the Cambridge Neuropsychological Test Automated Battery (CANTAB), which has shown sensitivity to cognitive dysfunction across different clinical groups, including patients with MS. Objective: The objective of the study was to assess the cognitive functions with CANTAB battery in MS patients during relapse, in stable MS patients, and healthy controls, and to establish the timing and pattern of cognitive recovery after relapse. Methods: Sixty relapsing, thirty stable MS patients, and thirty controls were assessed with CANTAB. The relapse group was assessed during multiple sclerosis relapse and one and three months after the first assessment. Results: The results of medium difficulty tasks of spatial planning, episodic visual recall and working memories were worse in relapse group than in stable MS group (p<0.05). The results of difficult tasks were worse in relapse and stable MS groups than in controls (p<0.05). The most significant improvement of speed of response, spatial planning, episodic visual recall memory and spatial working memory was established at one month after the first assessment, additional improvement of spatial planning and working memory was observed at three months after the first assessment. Conclusions: The results of this study confirm that cognitive function is affected during MS relapse. CANTAB battery tests which assess the spatial planning, episodic visual memory and working memory showed MS relapse-related cognitive dysfunction. Significant improvement of the speed of response, spatial planning, episodic visual recall and working memory was established at one month after MS relapse. The additional improvement in executive functions, spatial planning, and working memory was observed at three months after MS relapse.